Perovskite solar cell semi-transparent hollow carbon electrode and preparation method thereof
Patent Information
- Application Number
- CN202310794635.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-06-30
AI Technical Summary
[0006]本发明的目的在于针对现有技术存在的问题和不足,提供一种用于钙钛矿太阳能电池半透明镂空碳电极,可有效解决现有钙钛矿太阳能半透明电极成本高、制备困难,稳定性差等问题
[0045](1)传统钙钛矿太阳能电池需要采用金、银等贵金属电极,通常需要大规模真空蒸发设备才能制备,其成本非常高且无法回收,造成极大浪费;本发明采用廉价的碳材料作为钙钛矿太阳能电池的背电极,无需真空蒸发设备,采用廉价的丝网印刷工艺或者刮刀涂布等工艺即可制备,极大降低了制造和生产成本。
Smart Images

Figure HDA0004314592270000011 
Figure HDA0004314592270000012 
Figure HDA0004314592270000013
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrode technology, specifically relating to a semi-transparent hollow carbon electrode for perovskite solar cells and its preparation method. Background Technology
[0002] Over the past decade, the electrical efficiency of perovskite solar cells has rapidly climbed to over 25%. Metal halide perovskites are highly efficient light absorbers with high carrier mobility; perovskite solar cells can be manufactured at low temperatures using scalable solution processes, reducing manufacturing costs and enabling the fabrication of large-area building-integrated photovoltaic (BIPV) equipment.
[0003] Existing perovskite solar cells typically use precious metal electrodes such as gold and silver. These electrodes are expensive, opaque, and only allow light to be received from one side, failing to improve light energy utilization and making them unsuitable for the fabrication of BIPV modules such as photovoltaic glass and photovoltaic skylights. While DMD electrodes using MoO3 / Au / MoO3 can achieve a certain degree of transparency and allow light to be received from both sides, their fabrication requires a high vacuum environment and involves significant time and energy consumption, resulting in high costs. Furthermore, during use, the thin gold layer of the DMD electrode gradually agglomerates into isolated island structures, which greatly increases the electrode resistance and significantly impacts the current and conversion efficiency of the solar cell device. Using inherently transparent silver nanowire electrodes (AgNWs) can effectively avoid the micro-agglomeration problem during use, and AgNWs electrodes can be fabricated by spraying in an atmospheric environment, effectively reducing costs while expanding production area. However, perovskite solar cell materials themselves contain a large number of halide ions, and silver nanowires exposed to a halide ion environment will corrode rapidly, also leading to a significant decrease in device performance. In addition, indium tin oxide (ITO) electrodes are also very popular transparent electrodes with high transmittance, but the electrodes themselves have low conductivity, slow deposition rate, and the fabrication process requires large vacuum equipment such as magnetron sputtering, which makes it impossible to reduce costs and still unsuitable for the fabrication of semi-transparent solar cells.
[0004] Using inexpensive carbon electrodes can effectively reduce the fabrication cost of solar cells, and the fabrication process does not require large-scale vacuum equipment. The inherent hole transport capability of carbon materials can also reduce or eliminate the need for hole transport materials in perovskite solar cells, further lowering production costs. However, currently used carbon electrodes are all quite thick (>10 μm) and completely cover the entire electrode area, making it impossible to achieve semi-transparency. Furthermore, the very few devices that achieve semi-transparency suffer from significant efficiency losses due to poor top electrode contact performance, leading to reduced stability.
[0005] Therefore, further exploration of the efficient application of low-cost carbon electrodes in the field of semi-transparent solar cells is of great research and application significance. Summary of the Invention
[0006] The purpose of this invention is to address the problems and shortcomings of existing technologies by providing a semi-transparent hollow carbon electrode for perovskite solar cells, which can effectively solve the problems of high cost, difficult preparation, and poor stability of existing perovskite solar cell semi-transparent electrodes.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] A semi-transparent perforated carbon electrode for a perovskite solar cell includes a perforated carbon electrode and an auxiliary conduction intermediate layer disposed on its surface; the surface of the perforated carbon electrode is provided with an array of perforated holes at intervals; the auxiliary conduction intermediate layer includes a KCl layer, a PEG layer and a barrier layer disposed sequentially.
[0009] In the above scheme, the KCl layer and the peg layer are coated with KCl solution and peg solution respectively, and then dried; the concentration of KCl is 10-15 mg / ml, and the concentration of peg is 3-5 mg / ml.
[0010] Furthermore, the coating step employs a spin coating process with a spin coating speed of 2000-3000 rpm.
[0011] In the above scheme, the barrier layer is an ITO layer or a 2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine))9,9′-spirodifluorene (Spiro-OMeTAD) layer.
[0012] In the above scheme, the hollow holes account for 10-50% of the surface area of the hollow carbon electrode.
[0013] In the above scheme, the equivalent diameter of the hollow hole is 1-3mm.
[0014] In the above scheme, the distance between two adjacent perforated holes is 7-11mm.
[0015] Preferably, the perforated hole is circular or hexagonal in shape.
[0016] In the above scheme, the hollow carbon electrode is first prepared by using modified carbon slurry as raw material to prepare a carbon electrode wet film, then dried and sintered, and then hollowed out according to the hollow hole design requirements.
[0017] In the above scheme, the carbon electrode wet film is formed by methods such as screen printing, doctor blade coating, slit extrusion, or casting.
[0018] Furthermore, when using screen printing, the screen printing plate is set up according to the design requirements of the perforation, and then screen printing is performed to directly obtain a carbon electrode wet film with a perforated structure.
[0019] In the above scheme, the hollowing process step uses laser processing, mechanical processing or other methods to perform local hollowing processing on the carbon electrode.
[0020] In the above scheme, the raw materials and their mass percentages in the modified carbon slurry include: 20-50% conductive matrix, 30-61% dispersant, 0-15% binder, 0-8% modifier, and 0-2% surfactant.
[0021] Furthermore, the conductive matrix can be selected from one or more of carbon black (including carbon nanospheres, acetylene black, furnace black, iron carbon black, and thermal black), graphene, graphite sheets, silver powder, and zinc powder; the dispersant can be selected from one or more of α-terpineol, tert-butanol, n-butanol, ethanol, propanol, isopropanol, propylene glycol, ethyl acetate, n-butyl acetate, benzene, toluene, xylene, acetone, diacetone alcohol, and ethylene glycol ethyl ether; the binder can be selected from one or more of acrylic resin, vinyl resin, phenolic resin, epoxy resin, polyvinylidene fluoride, polyacrylic acid, polytetrafluoroethylene, and polyvinyl alcohol; and the modifier can be selected from one or more of isopropyl titanate, copper powder, zinc powder, iron powder, and carbon nanotubes.
[0022] Preferably, in the modified carbon slurry, the binder accounts for 2-10% by mass; the modifier accounts for 3-5% by mass; and the surfactant accounts for 1.5-5% by mass.
[0023] Preferably, the dispersant is ethyl acetate.
[0024] Preferably, the selected surfactant can be one or more of lecithin, amino acids, etc.
[0025] Furthermore, the present invention uses mechanical grinding, ball milling, stirring, and vibration to mix the raw materials evenly to obtain the modified carbon paste; the introduction of surfactants such as lecithin solution into the carbon paste helps to assist the carbon paste in screen printing.
[0026] In the above scheme, the modified carbon paste can also be a diluted commercially available conductive carbon paste; the commercially available carbon paste is JELCON CH-10 or CH-8 conductive carbon paste, and the diluent used is ethyl acetate; the volume ratio of the diluent to the commercially available conductive carbon paste is 1:(4-8).
[0027] Preferably, a surfactant is further introduced into the commercially available conductive carbon paste.
[0028] The above-mentioned method for preparing a semi-transparent perforated carbon electrode for a perovskite solar cell includes the following steps:
[0029] (1) Preparation of carbon electrode wet film: An assisting conduction intermediate layer (the perovskite substrate is in contact with the KCl layer) is set on the perovskite substrate, and the modified carbon slurry is set on the barrier layer of the assisting conduction intermediate layer of the perovskite substrate to form a carbon electrode wet film.
[0030] (2) Sintering of carbon electrode: The perovskite substrate on which the carbon electrode wet film is disposed is sintered; a conductive carbon film is formed on the surface of the perovskite substrate.
[0031] (3) Post-processing of carbon electrode: The obtained conductive carbon film is hollowed out to obtain the semi-transparent hollowed-out carbon electrode of the perovskite solar cell.
[0032] In the above scheme, the intermediate layer for assisting conduction includes a KCl layer, a PEG layer and a barrier layer arranged in sequence. The KCL layer is mainly used to passivate defects in the perovskite layer, while PEG acts as a p-type polymer to conduct. The two functional layers work together to effectively assist conduction between the perovskite layer and the hollowed-out electrode, thereby improving device performance (stability, etc.).
[0033] In the above scheme, the thickness of the KCl layer is 5-8 nm; the thickness of the PEG layer is 6-10 nm.
[0034] Preferably, the barrier layer is ITO, prepared by magnetron sputtering, with a sputtering thickness of 50-200 nm and a sputtering rate of 0.14-0.16 A / S.
[0035] Preferably, the third barrier layer is 2,2′,7,7′-tetra(N,N-di-p-methoxyphenylamine))9,9′-spirodifluorene (Spiro-OMeTAD); it is prepared by spin coating process with a spin coating speed of 1500-4000 rpm and a time of 15-40 s.
[0036] In the above scheme, the carbon electrode wet film is formed by methods such as screen printing, doctor blade coating, slit extrusion, or casting.
[0037] In the above scheme, the screen printing step includes: placing the perovskite substrate with the auxiliary conduction intermediate layer on the printing machine stage, setting the screen printing plate with the corresponding pattern according to the designed cutout holes and their step-by-step rules, then clamping it on the printing machine, attaching and aligning the screen printing plate with the substrate, loading modified carbon paste onto one end of the screen printing plate, and using a squeegee to evenly spread the paste to fill the entire pattern area, maintaining a certain pressure and repeating the operation several times.
[0038] Preferably, the wet film preparation method in step (4) above is screen printing. The screen pattern is a neatly arranged circle or hexagon with an equivalent diameter of 1-3 mm. The screen pattern has a cutout ratio of 10-50%, the mesh count of the screen is 40-400 mesh, the squeegee tilt angle is 50-80°, the squeegee hardness is 60-85°, and the screen printing speed is 10-100 mm / s.
[0039] Preferably, the wet film preparation method in step (4) above is blade coating, the gap between the blade and the substrate is 50-350 μm, and the blade coating speed is 2-40 mm / s.
[0040] In the above scheme, the sintering step is performed at a temperature of 80-150℃ for a time of 5-30 minutes.
[0041] In the above scheme, the laser processing steps are as follows: set up the pattern array to be laser processed, place the dried and sintered carbon electrode on the laser stage, set the laser power to 18-36W and the frequency to 50-150kHz, and remove the excess electrode part by laser to make it semi-transparent.
[0042] Furthermore, the perovskite substrate includes a conductive glass, an electron transport layer, a perovskite light-absorbing layer, and a conduction-assisting intermediate layer arranged sequentially.
[0043] The titanium dioxide solar cell prepared according to the above scheme can achieve controllable adjustment of transmittance from 10-45% based on the carbon mesh design. At the same time, the multi-layer structure design of the assisting conduction layer can effectively improve problems such as carrier loss and improve the contact effect between the top electrode and the top electrode, thus effectively ensuring and improving the efficiency and stability of the obtained semi-transparent perovskite solar cell. The photoelectric conversion efficiency of the obtained semi-transparent perovskite solar cell can reach 9.65%; after being placed for 5600 hours, it can still reach more than 95% of the initial efficiency.
[0044] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0045] (1) Traditional perovskite solar cells require precious metal electrodes such as gold and silver, which usually require large-scale vacuum evaporation equipment to prepare. The cost is very high and cannot be recycled, resulting in great waste. This invention uses inexpensive carbon materials as the back electrode of perovskite solar cells. No vacuum evaporation equipment is required. They can be prepared using inexpensive screen printing or doctor blade coating processes, which greatly reduces manufacturing and production costs.
[0046] (2) The present invention uses direct patterning printing, laser or mechanical processing post-processing methods, combined with an assisting conduction intermediate layer, to make the carbon electrode partially hollow; while achieving a semi-transparent effect, it can effectively ensure device efficiency; compared with semi-transparent electrodes such as ITO, AgNWs, and DMD, the hollow carbon electrode obtained by the present invention has excellent stability, very low manufacturing cost, and is not prone to problems such as the decline in the performance of the entire device due to electrode aging during the operation of solar cells.
[0047] (3) To solve the problem of carrier collection in the hollow part of the electrode, an assisting conduction layer is introduced between the perovskite and carbon electrodes. This can effectively ensure that more photogenerated electrons can be collected by the electrode area, thereby achieving higher photoelectric conversion efficiency, while also ensuring good stability. Attached Figure Description
[0048] Figure 1 The diagram shows the perovskite solar cell structure described in each embodiment of the present invention.
[0049] Figure 2 This is a schematic diagram showing the properties of the carbon electrode slurry obtained in Example 1 of the present invention;
[0050] Figure 3 This is a design drawing of the screen printing template (screen printing plate) used in Embodiment 1 of the present invention;
[0051] Figure 4 This is a morphological diagram of the semi-transparent carbon electrode obtained in Example 1 of the present invention;
[0052] Figure 5 This is a top view of the perovskite solar cell obtained in Example 1 of the present invention.
[0053] Figure 6 This is the ultraviolet-visible transmittance curve of the perovskite solar cell obtained in Example 1 of the present invention;
[0054] Figure 7 This is a cross-sectional scanning electron microscope image of the perovskite solar cell applied in Embodiment 1 of the present invention;
[0055] Figure 8 This is a morphological diagram of the semi-transparent carbon electrode obtained in Example 2 of the present invention;
[0056] Figure 9 This is a top view of the perovskite solar cell obtained in Example 2 of the present invention.
[0057] Figure 10 This is a cross-sectional scanning electron microscope image of the perovskite solar cell obtained in Example 2 of the present invention;
[0058] Figure 11This is a morphological diagram of the semi-transparent carbon electrode obtained in Example 3 of the present invention;
[0059] Figure 12 This is a top view of the perovskite solar cell obtained in Example 3 of the present invention.
[0060] Figure 13 This is a cross-sectional scanning electron microscope image of the perovskite solar cell obtained in Example 3 of the present invention;
[0061] Figure 14 This is a comparison chart of the photoelectric conversion efficiency of the perovskite solar cells obtained in Examples 1, 2, and 3 of the present invention and Comparative Examples 1 and 2.
[0062] Figure 15 This is a comparison chart of the photoelectric conversion efficiency of the perovskite solar cells obtained in Examples 1, 2, and 3 of the present invention and Comparative Examples 3 and 4.
[0063] Figure 16 This is a schematic diagram of the properties of the carbon electrode slurry obtained in Example 4 of the present invention.
[0064] Figure 17 This is a comparison chart of the normalized efficiency stability of the perovskite solar cells obtained in Example 4 and Comparative Example 5 of the present invention. Detailed Implementation
[0065] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0066] In the following embodiments, the method for fabricating the perovskite substrate with the assisting conductive intermediate layer includes the following steps:
[0067] 1) Cleaning FTO conductive glass: Use deionized water and 99% alcohol to sonicate for 15 minutes each, then blow dry and let stand;
[0068] 2) Preparation of electron transport layer: Place the cleaned conductive glass on a spin coater, rotate the alfa-SnO2 (13mg / ml) solution at 3000r / min for 30s, then anneal at 150℃ for 30min, and then take it out and place it.
[0069] 3) Preparation of perovskite layer: 104.53 mg lead bromide (PbBr2) and 35 mg formammonium bromide (FABr) were dissolved in a polar solvent (160 μl DMF + 40 μl DMSO) to obtain a perovskite precursor, which was placed in a shaker for 1 h; the substrate obtained in 2) was placed on a doctor blade coater, and the prepared perovskite solution was taken and coated at a speed of 10 mm / s under nitrogen pressure to prepare a uniform perovskite film;
[0070] 4) Preparation of the first two substrate layers of the assisting conductive layer: KCL layer and PEG layer are prepared by spin-coating KCL solution and PEG solution respectively. The concentration of KCL solution is 30 mg / ml and the concentration of PEG solution is 6 mg / ml. The spin-coating is carried out at a speed of 3000 r / min for 45 s, and then dried at 100℃ for 15 min to obtain the perovskite substrate.
[0071] 5) Preparation of the third barrier layer: Prepare Spiro-OMeTAD solution; the specific ratio is 73 mg Spiro-OMeTAD, 9.36 mg Li-TFSI, 8.7 mg Co-TFSI, 30 μL tBp, and 1 mL chlorobenzene. After adding these to a weighing bottle, place it in a vortex mixer and shake for 30 min. Load 30 μL of Spiro-OMeTAD solution onto the perovskite substrate with the obtained conductive intermediate layer and spread it evenly. Spin coat it on a spin coater at 3000 RPM for 30 s and then remove it.
[0072] Example 1
[0073] A perforated carbon electrode for a perovskite solar cell; perovskite solar cell (see schematic diagram). Figure 1 The preparation method includes the following steps:
[0074] (1) Add 0.5g conductive carbon black (37%), 0.1g graphite flakes (7.4%), 0.7g α-terpineol (51.9%), and 0.05g isopropyl titanate (3.7%) to an agate mortar and grind until a uniform, particle-free carbon electrode slurry is obtained (see...). Figure 2 );
[0075] (2) Mix the above slurry with ethyl acetate at a mass ratio of approximately 9:2, and stir and dilute it using a stirring rod; the components and their mass ratios in the resulting diluted slurry are as follows: conductive matrix 36.3% (conductive carbon black 30.3%, graphite flakes 6.0%), diluent 60.7% (α-terpineol 42.5%, ethyl acetate 18.2%), and isopropyl titanate 3.0%;
[0076] (3) Load the above-mentioned uniformly mixed paste onto the screen printing stencil (screen printing plate, see...). Figure 3 On the screen, the screen pattern is a neatly arranged regular hexagon with a side length of 2mm, a cutout ratio of 35%, and a mesh size of 400. The perovskite substrate with the intermediate layer for assisting conduction is placed on the printing press and aligned with the screen. The paste is then forcefully scraped over with a squeegee to completely cover the pattern on the screen. This process is repeated 3-5 times to obtain a wet film with cutout carbon electrodes.
[0077] (4) Place the obtained carbon electrode wet film on a hot table at 120°C and heat it for 10 minutes to dry it, thus obtaining a sintered and solidified hollow carbon electrode (see Figure 4 Simultaneously, the titanium dioxide solar cell device (see...) was obtained. Figure 5 ).
[0078] The photoelectric conversion efficiency of the prepared perovskite solar cell device was tested. The specific operation was as follows: the perovskite solar cell was connected to the test circuit and placed under an AM1.5G standard solar simulator, using an area of 0.14 cm². 2 The photoelectric conversion curve and efficiency of the solar cell were measured using a specified irradiation area of the shading plate, an instrument scanning rate of 0.1V / s, a voltage range of 1.6V to -0.1V, and a settling time of 100ms.
[0079] The average transmittance (AVT) in the visible light region was measured during the fabrication of the perovskite solar cell. The specific procedure was as follows: First, the UV-Vis spectrophotometer was calibrated to 100% transmittance with air as the background. Then, the substrate to be tested was mounted on the test stage, exposing the entire electrode area to the test area. The scanning range was 380-780 nm, and the scanning speed was 5 nm / s. The UV-Vis transmittance curve was obtained (see...). Figure 6 It has a considerable transmittance.
[0080] The cross-sectional scanning mirror image of the titanium dioxide solar cell device obtained in this embodiment is shown below. Figure 7 As can be seen, its top electrode is tightly bonded to the perovskite layer.
[0081] Example 2
[0082] A perovskite solar cell with a hollowed-out carbon electrode and a perovskite solar cell are disclosed. The preparation method is largely the same as that in Example 1, except that the preparation of the carbon electrode paste and the post-processing steps are different, as detailed below:
[0083] (1) Take 18g (12mL) of Japanese Jujo CH-10 carbon ink and 3mL of ethyl acetate into a weighing bottle, stir with a stirring rod until uniform, cover the weighing bottle, place it on a vortex shaker and shake at 2000RPM for 30min to obtain carbon electrode slurry.
[0084] (2) The obtained carbon electrode is placed on the stage of a nanosecond laser with a laser power of 40W, a frequency of 80kHz, and a scanning rate of 500mm / s. An array of regular hexagonal holes with a diameter of 2mm is uniformly etched on the carbon electrode, with a distance of 7mm between the hexagons.
[0085] Example 3
[0086] A perovskite solar cell with a hollowed-out carbon electrode and a perovskite solar cell are prepared using a method largely the same as in Example 1, except that the intermediate layer between the perovskite and the carbon electrode is different, as detailed below:
[0087] A third barrier layer, indium tin oxide (ITO) substituted for 2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine))9,9′-spirodifluorene (Spiro-OMeTAD), was prepared on the obtained perovskite layer by magnetron sputtering. The specific steps were as follows: the obtained perovskite layer was placed in a magnetron sputtering instrument with a sputtering vacuum of 3.75 × 10⁻⁶. -5 torr, sputtering rate 0.18 A / s, sputtering thickness 90 nm.
[0088] Example 4
[0089] A perforated carbon electrode for a perovskite solar cell and a perovskite solar cell are prepared in a manner similar to that of Example 1, except that a lecithin surfactant solution is further introduced into the carbon slurry, with a concentration of 40 mg / ml. The solution is stirred evenly with a glass rod and then 600 μl (lecithin accounts for 1.75% of the total slurry mass) is added dropwise.
[0090] Comparative Example 1
[0091] A titanium-ore solar cell metal electrode and a perovskite solar cell, the fabrication method of which includes the following steps:
[0092] (1) Prepare Spiro-OMeTAD solution; the specific ratio is 73mg Spiro-OMeTAD, 9.36mg Li-TFSI, 8.7mg Co-TFSI, 30μL tBp, and 1mL chlorobenzene. After adding these to the weighing bottle, place it in a vortex shaker and shake for 30min.
[0093] (2) Load 30uL Spiro-OMeTAD solution onto the obtained perovskite substrate with the intermediate layer for assisting conduction and spread it evenly. Then, spin it on a spin coater at 3000RPM for 30s and remove it.
[0094] (3) Apply adhesive tape to the electrode areas of the above substrates and then fix them into the high vacuum evaporation coating instrument. The working vacuum is 6*10. -4 Pa, evaporation rate 1A / s, evaporation of a 100nm thick gold electrode.
[0095] Comparative Example 2
[0096] A titanium-ore solar cell metal electrode and a perovskite solar cell are prepared using methods largely the same as those in Comparative Example 1, except that the vapor deposition process and electrode materials used are different, as detailed below:
[0097] The obtained substrate is fixed onto a high-vacuum evaporation coating equipment with a working vacuum of 2*10. -3 Pa, evaporation rate 2 A / s, evaporation of a 100 nm thick silver electrode
[0098] Comparative Example 3
[0099] A titanium-ore solar cell metal electrode and a perovskite solar cell are prepared using methods largely the same as those in Comparative Example 1, except that the vapor deposition process and electrode materials used are different, as detailed below:
[0100] The obtained substrate is fixed onto a high-vacuum evaporation coating equipment with a working vacuum of 6*10. -4 At pa, the evaporation rate was 0.1 A / s, and a 5 nm thick MoO3 was deposited. After a 5-minute interval, the evaporation rate was 0.1 A / s, and an 8 nm thick gold electrode was deposited.
[0101] Comparative Example 4
[0102] A titanium-ore solar cell metal electrode and a perovskite solar cell are prepared using methods largely the same as those in Comparative Example 1, except that the vapor deposition process and electrode materials used are different, as detailed below:
[0103] The obtained substrate is fixed onto a high-vacuum evaporation coating equipment with a working vacuum of 6*10. -4 At a deposition rate of 0.1 A / s, a 5 nm thick MoO3 layer was deposited. The substrate was then transferred to a magnetron sputtering deposition system with a working vacuum of 3.75 × 10⁻⁶. -5 torr, sputtering rate 0.18 A / s, sputtering thickness 180 nm.
[0104] Figure 14 The graph shows a comparison of the photoelectric conversion efficiency of perovskite solar cells obtained in Examples 1, 2, and 3 of the present invention with those in Comparative Examples 1 and 2. The results show that Examples 1, 2, and 3 have certain performance advantages over Comparative Examples 1 and 2.
[0105] Figure 15 The graph shows a comparison of the photoelectric conversion efficiency of perovskite solar cells obtained in Examples 1, 2, and 3 of this invention with those in Comparative Examples 3 and 4. The results show that Examples 1, 2, and 3 have certain performance advantages over Comparative Examples 3 and 4.
[0106] Comparative Example 5
[0107] A perovskite solar cell with a hollow carbon electrode and a perovskite solar cell are prepared in a manner similar to that of Example 1, except that we do not add an assisting conductive layer and do not add a certain amount of lecithin solution (surfactant) to the carbon paste.
[0108] Figure 17 The graph shows a comparison of the normalized efficiency stability of the perovskite solar cells obtained in Example 4 and Comparative Example 5 of the present invention. It can be seen that the stability of the perovskite solar cells obtained by the present invention is extended. By using optimization methods such as surfactants and multilayer assistive conduction layers, the actual contact area of the cell can be increased, which can effectively improve the conduction capacity and facilitate the formation of a stable device structure.
[0109] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A translucent perforated carbon electrode for a perovskite solar cell, characterized in that, It includes a hollow carbon electrode and an intermediate layer for assisting conduction disposed on its surface; the surface of the hollow carbon electrode is provided with an array of hollow holes arranged at intervals; the intermediate layer for assisting conduction includes a barrier layer, a PEG layer and a KCl layer disposed in sequence.
2. The semi-transparent perforated carbon electrode according to claim 1, characterized in that, The KCl layer and the PEG layer are formed by coating and drying with KCl solution and PEG solution, respectively; the concentration of KCl is 10-15 mg / ml and the concentration of PEG is 3-5 mg / ml.
3. The semi-transparent perforated carbon electrode according to claim 1, characterized in that, The barrier layer is an ITO layer or a Spiro-OMeTAD layer.
4. The semi-transparent perforated carbon electrode according to claim 1, characterized in that, The perforated holes occupy 10-50% of the surface area of the perforated carbon electrode.
5. The semi-transparent perforated carbon electrode according to claim 1, characterized in that, The hollow carbon electrode is prepared by first preparing a carbon electrode wet film using modified carbon slurry as raw material, then drying and sintering it, and finally hollowing it out according to the hollow hole design requirements.
6. The semi-transparent perforated carbon electrode according to claim 5, characterized in that, The modified carbon slurry contains the following raw materials and their mass percentages: 20-50% conductive matrix, 30-60% dispersant, 0-15% binder, 0-8% modifier, and 0-2% surfactant.
7. The translucent perforated carbon electrode according to claim 6, characterized in that, The conductive matrix is one or more of carbon black, graphene, graphite sheets, silver powder, and zinc powder; the dispersant is one or more of α-terpineol, tert-butanol, n-butanol, ethanol, propanol, isopropanol, propylene glycol, ethyl acetate, n-butyl acetate, benzene, toluene, xylene, acetone, diacetone alcohol, and ethylene glycol ethyl ether; the binder is one or more of acrylic resin, ethylene resin, phenolic resin, epoxy resin, polyvinylidene fluoride, polyacrylic acid, polytetrafluoroethylene, and polyvinyl alcohol; the modifier is one or more of isopropyl titanate, copper powder, zinc powder, iron powder, and carbon nanotubes; and the surfactant is lecithin or amino acids.
8. A method for preparing a translucent perforated carbon electrode for a perovskite solar cell according to any one of claims 1 to 7, characterized in that, Includes the following steps: (1) Preparation of carbon electrode wet film: An assisting conduction intermediate layer is set on a perovskite substrate, and modified carbon slurry is set on the barrier layer of the assisting conduction intermediate layer of the perovskite substrate to form a carbon electrode wet film. (2) Drying and sintering of carbon electrodes: Sintering the perovskite substrate with a wet carbon electrode film; forming a conductive carbon film on the surface of the perovskite substrate. (3) Post-processing of carbon electrode: The obtained conductive carbon film is hollowed out to obtain the semi-transparent hollowed-out carbon electrode of the perovskite solar cell.
9. The preparation method according to claim 8, characterized in that, The perovskite substrate includes a conductive glass, an electron transport layer, and a perovskite light-absorbing layer arranged sequentially.
10. The preparation method according to claim 8, characterized in that, The sintering step is performed at a temperature of 80-150℃ for 5-30 minutes.
Citation Information
Patent Citations
A method in a small organic molecule trans-perovskite solar cell
CN109065730A
Semitransparent hollow perovskite solar cell and preparation method thereof
CN112382727A